Straty materialne Kościoła katolickiego na terenie diecezji kieleckiej w czasie II wojny światowej - Karkocha, Małgorzata (Przegląd Nauk Historycznych, 2015)
During the Second World War Catholic Church in the Diocese of Kielce suffered significant losses in church buildings, their equipment, objects of worship, parish account books, church libraries and graveyards. These losses were caused by both military operations and predatory policy of the German occupiers. The largest losses suffered parishes located in the area near the Baranów and San-domierz bridgehead, where from August 1944 to January 1945 bloody fighting took place. In these areas, there were destroyed almost the entire villages together with their residential buildings, outbuildings, vicarages, churches and other sacra buildings. Based on materials stored in the Archives of the Diocese of Kielce it can be said, that about 20 objects of worship were destroyed in a degree exceeding 70%, slightly more than 20 in the range of 30–70%, and 70 on a scale of less than 30%. Destruction of churches included their furnishings as well. In many parishes, robes and liturgical books, paraments, votive offerings and even parish records registering births, marriages and deaths were lost. Devastation of Catholic churches and looting of cultural property was an integral aspect of the Nazis fight with Polish culture.